Mapping competency frameworks: implications for public health curricula design. (12th May 2022) - Coombe, Leanne; Severinsen, Christina Anne; Robinson, Priscilla
Abstract: Objectives: We discuss the implications stemming from a recent competency mapping project on public health workforce education and training programs. Methods: In line with professional practice, we reflected on the results of a major mapping exercise which examined public health competency frameworks against the Global Charter, particularly with respect to the implications for curriculum design. Results: Our reflections identified five key challenges (diversity of frameworks, interpretation challenges, levels of competence, integration in curricula and knowledge vs skills‐based competences) for developing internationally consistent credentialling standards. Conclusions: While the Charter provides an international benchmark for public health curricula, we argue that applying an international competency framework is challenging. Anyone working in public health should be trained in all foundation areas of public health to support public health practice and initiatives into the future and they may then choose to specialise in sub‐disciplines of public health. Implications for public health: Both theoretical and practical content must be fully integrated across public health programs to operationalise competencies. Utilising the Charter can ensure alignment with the sector needs, and curriculum mapping should be an integral part of a continual and ongoing review process.